Membangun Pemahaman Operasi Hitung Dasar Siswa melalui Permainan Tradisional Congklak - Zahara Taufani; Uswatun Hasanah; Herjan Haryadi; Muhamad Akrom (cendekia citra gemilang, 2026)
Understanding addition and subtraction is an important foundation in low-grade math learning. However, grade II students in one of the elementary schools in West Lombok still have difficulty understanding the concept concretely. This research aims to improve the understanding of addition and subtraction through the application of the traditional game of congklak. This research uses Classroom Action Research (PTK) which is carried out in two cycles. Each cycle includes the stages of planning, action, observation, and reflection. The subject of the study was a grade II student in one of the elementary schools in West Lombok. Data was collected through learning outcome tests, observation of student and teacher activities, and documentation. The results of the study showed an increase in student understanding. The average cognitive score increased from 74.66 in the first cycle to 86.66 in the second cycle. Learning completeness increased from 56.66% to 80%. In addition, the affective aspect of students also increased from 57.5% to 92.5%. Thus, congklak games can be used as a concrete and fun medium to help students understand basic counting operations. These findings suggest that traditional games have the potential to support active, contextual, and meaningful math learning.